2019
DOI: 10.3389/fgene.2019.01127
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Maintaining Family Diversity in Commercially Mass-Spawned Penaeid Shrimp: A Case Study on Penaeus monodon

Abstract: Skewed family distributions are common in aquaculture species that are highly fecund, communally (mass) spawned, and/or communally reared. The magnitude of skews pose challenges for maintaining family-specific genetic diversity, as increased resources are required to detect individuals from underrepresented families, or reliably determine relative survival as a measure of family performance. There is limited understanding of family skews or changes in family proportion of communally reared shrimp under commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The similar condition was described in Premachandra et al [ 3 ], where they found the SNP pedigrees tended to split part of the full-sib families determined by microsatellites into smaller groups or produced single individuals unrelated to any other members. Moreover, the default low genotyping error rate of 0.01% to 1% seemed too low even for a relatively low-density SNP panel [ 80 ], allowing only for ≤ 2 genotyping errors for a whole panel of 208 SNPs, which might cause interference to a certain extent and lead to the erroneous assignment of parents. Hall et al [ 40 ] detected a genotyping error rate of 5% in GBS data, which suggested a finer selection of SNP loci would be needed to alleviate the consequence brought by such kind of error.…”
Section: Discussionmentioning
confidence: 99%
“…The similar condition was described in Premachandra et al [ 3 ], where they found the SNP pedigrees tended to split part of the full-sib families determined by microsatellites into smaller groups or produced single individuals unrelated to any other members. Moreover, the default low genotyping error rate of 0.01% to 1% seemed too low even for a relatively low-density SNP panel [ 80 ], allowing only for ≤ 2 genotyping errors for a whole panel of 208 SNPs, which might cause interference to a certain extent and lead to the erroneous assignment of parents. Hall et al [ 40 ] detected a genotyping error rate of 5% in GBS data, which suggested a finer selection of SNP loci would be needed to alleviate the consequence brought by such kind of error.…”
Section: Discussionmentioning
confidence: 99%
“…This was to keep the population size per generation as close as possible to number of individuals per generation in S1 (5000). In addition, the allocation of the number of progeny and their respective distribution was based on the study of maintaining the genetic diversity in P. monodon carried out by Foote, et al 50 . They found that the highest contribution of a single family for P. monodon bred in captivity was 18%.…”
Section: Methodsmentioning
confidence: 99%
“…genomic selection (GS), has been widely adopted for enhancing commercial traits in animal breeding 6 . In aquaculture for example, GS has been shown to predict breeding values (BV) more accurately for growth traits in Atlantic salmon 7 , common carp 8 , Nile tilapia 9 , channel catfish 10 , large yellow croaker 11 , yellowtail kingfish 12 , yellow drum 13 , Pacific oyster 14 , scallop 15 , 16 , whiteleg shrimp 17 and banana shrimp 18 compared to pedigree-based BV predictions and has recently been reviewed for applications in aquaculture by Zenger et al 19 . GS uses the information obtained from genotypic markers to improve the accuracy of BVs.…”
Section: Introductionmentioning
confidence: 99%
“…Quite often it is not possible to manually tag or separate family lines. As a result, genotyping progeny and broodstock, and assigning parentage through molecular means is essential as it enables the recovery of pedigree information and ensures breeding programs are managed effectively [27,58].…”
Section: Assay Utilisation Parentage Assignmentmentioning
confidence: 99%
“…Since the progeny were the first generation of wild broodstock pairings, inbreeding was not included. Prior sib-ship assumptions were excluded allowing for highly skewed family sizes commonly observed in mass-spawning aquaculture systems [58]. Likewise maternal and paternal polygamy were allowed to account for potential of half-sib breeding designs that utilise artificial insemination.…”
Section: Parentage Assignmentmentioning
confidence: 99%